2014
DOI: 10.1186/1756-0500-7-746
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the SD BIOLINE HIV/syphilis Duo assay at a rural health center in Southwestern Uganda

Abstract: BackgroundPoint-of-care tests have the capacity to improve healthcare delivery by reducing costs and delay associated with care. A novel point-of-care immunochromatographic test for dual diagnosis of both HIV and syphilis by detecting IgG, IgM and IgA antibodies to HIV, and specific and recombinant Treponema pallidum antigens has recently been developed, but has not been evaluated in rural field settings. We evaluated the performance of the SD Bioline Syphilis/HIV Duo (Duo) assay at a healthcare center in rura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
30
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 14 publications
9
30
1
1
Order By: Relevance
“…The performance of the SD Bioline test in our study is lower than that found in a previous evaluation which used laboratory personal and techniques to conduct the tests and reported sensitivities and specificities for both HIV and syphilis of 100% 9 10. Our results for detection of treponemal antibodies by the SD Bioline test are similar to other POCT evaluations where syphilis tests show a lower sensitivity compared with laboratory standards when evaluated in the field rather than the laboratory 11 12.…”
Section: Discussioncontrasting
confidence: 80%
“…The performance of the SD Bioline test in our study is lower than that found in a previous evaluation which used laboratory personal and techniques to conduct the tests and reported sensitivities and specificities for both HIV and syphilis of 100% 9 10. Our results for detection of treponemal antibodies by the SD Bioline test are similar to other POCT evaluations where syphilis tests show a lower sensitivity compared with laboratory standards when evaluated in the field rather than the laboratory 11 12.…”
Section: Discussioncontrasting
confidence: 80%
“…Our results are comparable to those of laboratory evaluations that were conducted previously with different point-of-care tests for HIV and treponemal antibody detection in sera and whole blood, which also yielded high performance values for sensitivity and specificity (1,(5)(6)(7)(11)(12)(13). In our evaluation, the sensitivity of the Chembio DPP HIV-syphilis rapid test to detect HIV antibodies was somewhat greater than its sensitivity to detect syphilis antibodies, in concurrence with several other studies (5,6,11,12,14).…”
supporting
confidence: 90%
“…Previous studies evaluated dual tests for antibodies to HIV and T. pallidum, including the MedMira Multiplo (MedMira; Halifax, Nova Scotia, Canada), the SD BIOLINE HIV/Syphilis Duo test (Standard Diagnostics; Gyeonggi-do, Republic of Korea), and the Chembio DPP HIV-syphilis assay (Chembio Diagnostics; Medford, NY) (7,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). These dual tests demonstrated sensitivities and specificities for HIV antibody detection ranging from 93.8% to 100% and 91.9% to 100%, respectively.…”
mentioning
confidence: 99%